1995
DOI: 10.1007/bf02207678
|View full text |Cite
|
Sign up to set email alerts
|

Microheterogeneity of acute phase proteins in patients with clinically active and clinically nonactive osteoarthritis

Abstract: Microheterogeneity of two acute phase glycoproteins, alpha-1-acid glycoprotein (AGP) and alpha-1-antichymotrypsin (ACT), concentrations of AGP, ACT, and C-reactive protein (CRP), and levels of three cytokines: interleukin 1 beta (IL-1-beta), interleukin 6 (IL-6), and tumor necrosis factor alpha (TNF-alpha) were determined in 61 serum samples and 7 synovial fluids (SFs) obtained from patients (n = 61) with osteoarthritis. Using affinity immunoelectrophoresis with concanavalin A (conA), a significant decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The presence of TNF␣ in synovial fluid and the increase in the densities of TNFRI and TNFRII on OA chondrocytes may imply an important role for this cytokine in the pathogenesis of OA. In support of this hypothesis, increased numbers of chondrocytes that synthesize IL-1␤ and TNF␣ have been found in OA cartilage (15,17). This may reflect the influence of TNF␣ in the synovial fluid, since many cell types in the synovium, such as macrophages, synovial fibroblasts, or chondrocytes themselves, could produce this cytokine.…”
mentioning
confidence: 49%
See 3 more Smart Citations
“…The presence of TNF␣ in synovial fluid and the increase in the densities of TNFRI and TNFRII on OA chondrocytes may imply an important role for this cytokine in the pathogenesis of OA. In support of this hypothesis, increased numbers of chondrocytes that synthesize IL-1␤ and TNF␣ have been found in OA cartilage (15,17). This may reflect the influence of TNF␣ in the synovial fluid, since many cell types in the synovium, such as macrophages, synovial fibroblasts, or chondrocytes themselves, could produce this cytokine.…”
mentioning
confidence: 49%
“…In the present experiments, we found that OA chondrocytes constitutively produced mRNA for TNF␣, TNF␤, IL-6, IFN␥, IFN␤, TGF␤1, and TGF␤3. Increased numbers of chondrocytes synthesizing TNF␣, IL-1␤, and IL-6 in OA cartilage also were identified by Hrycaj and coworkers (15) and by Shinmei and coworkers (17). The levels of many of these cytokines are affected by stimulation of the chondrocytes with TNF␣.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Using CAIE, Con A-reactive dibranched oligosaccharide chains of AGP increase in the sera of early-stage acute inflammation patients [14,16,17] but decrease in the sera of chronic inflammation patients. Examples are severe rheumatoid arthritis [14,15], alcoholic liver cirrhosis [19], pulmonary sarcoidosis [18], and osteoarthritis [20]. This indicates that different inflammatory mediators are involved in the regulation of the degree of branching of AGP in acute and chronic inflammation [21].…”
Section: Introductionmentioning
confidence: 97%